Copyright protection, in the light of the special abbreviated procedure and the private prosecutor figure (Law 1826) in the Colombian Criminal Law = La protección de los derechos de autor, a la luz del procedimiento especial abreviado y la figura del acusador privado (Ley 1826) en el Derecho penal colombiano = A proteção dos direitos de autor, à luz do procedimento especial abreviado e a figura do acusador privado (Lei 1826) no Direito penal colombiano - Cabrera Peña, Karen Isabel (Revista Criminalidad, 2018)
This paper aims to analyze the impact of Law 1826/2017 -of the special abbreviated procedure and the private prosecutor figure- in the case of non-criminal complaints, using as an example the crime of violation against property rights of the author to demonstrate through the legal dogmatic, that in most cases, the use of the punitive power of the state does not accomplish its purpose of sanctioning only those conducts that are particularly detrimental to the legal assets. This circumstance can result benefiting copyright holders with power in the market, even if the affectation might be minimal. Thus, it concludes that it is necessary to exclude crimes that infringe on the author’s property rights in case of processing by the special abbreviated procedure and the private prosecutor figure to accomplish the goals of the state’s punitive power.